Mechanical Micronization of Lipoaspirates: Squeeze and Emulsification Techniques. Issue 1 (January 2017) - Mashiko, Takanobu; Wu, Szu-Hsien; Feng, Jingwei; Kanayama, Koji; Kinoshita, Kaori; Sunaga, Ataru; Narushima, Mitsunaga; Yoshimura, Kotaro
Abstract : Background: Condensation of grafted fat has been considered a key for achieving better outcomes after fat grafting. The authors investigated the therapeutic potential of two mechanical tissue micronizing procedures: squeeze and emulsification. Methods: Human aspirated fat was centrifuged (centrifuged fat) and fragmented with an automated slicer (squeezed fat). Alternatively, centrifuged fat was emulsified by repeated transfer between two syringes through a small-hole connecter and then separated by mesh filtration into two portions: residual tissue of emulsified fat and filtrated fluid of emulsified fat. The four products were examined for cellular components. Results: Histologic and electron microscopic analyses revealed that squeezed fat and residual tissue of emulsified fat contained broken adipocytes and fragmented capillaries. Compared with centrifuged fat, the squeezed fat and residual fat products exhibited increased specific gravity and increased numbers of adipose-derived stem/stromal cells and endothelial cells per volume, suggesting successful cell/tissue condensation in both squeezed fat and residual tissue of emulsified fat. Although cell number and viability in the stromal vascular fraction were well maintained in both squeezed fat and residual fat, stromal vascular fraction culture assay showed that adipose-derived stromal cells were relatively damaged in residual tissue of emulsified fat but not in squeezed fat. By contrast, no adipose-derived stromal cells were cultured from filtrated fluid of emulsified fat. Conclusions: The authors' results demonstrated that mechanical micronization is easily conducted as a minimal manipulation procedure, which can condense the tissue by selectively removing adipocytes without damaging key components, such as adipose-derived stromal cells and endothelial cells. Depending on the extent of adipocyte removal, the product may be a useful therapeutic tool for efficient tissue volumization or therapeutic revitalization/fertilization. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V. Abstract : Supplemental Digital Content is available in the text.